Increased Risk of Tumor Necrosis Factor-Alpha Levels in Adult Patients with Malignancy Receiving Non-Leucodepleted Packed Red Cells Transfusion - Triyono, Teguh; Jati, Bambang Hendriawan Prasaja; Sukorini, Usi (Springer, 2022)
Background and Objectives: Blood transfusion in patients with malignancy may evoke transfusion reactions. Leukocyte, as a major producer of cytokines, including Tumor Necrosis Factor-alpha (TNF-alpha), is considered to correlate to transfusion reactions. This study aims to determine the risk of increased TNF-alpha in adult patients with malignancy who received non-leucodepleted (nLD) erythrocyte transfusion compared to those receiving leucodepleted (LD) Packed Red Cells (PRC) transfusion. Materials and Methods: This quasi-experimental study was conducted on adult patients with malignancy who required PRC transfusion and underwent outpatient treatment. The patients were divided without randomization into nLD and LD groups, and then their pre-transfusion TNF-alpha levels and the post-transfusion changes were examined. Results: This study included thirty-one patients fulfilling the inclusion criteria. The TNF- alpha levels in nLD and LD groups after transfusion increased significantly (p < 0.05), i.e., from 0.81 (0.2 - 4.2) pg/mL and 1.7 (0.15 - 6.3) pg/mL to 10.1 (1.4 - 28.9) and 5.9 (0.95 - 12.9) pg/mL. There was no significant difference in the pre-transfusion median TNF-alpha levels between the nLD and LD groups (p = 0.122). However, the post-transfusion median TNF-alpha levels of the nLD group were significantly higher (p = 0.024). It indicated that the increase in TNF-alpha levels is associated with nLD blood products transfused. The Relative Risk of the increased TNF-alpha levels in nLD-PRC transfusion was 2.01 (95% Confidence Interval: 1,153-3,502). Conclusion: nLD-PRC transfusion poses a 2.01 times risk for increased TNF-alpha levels compared to LD-PRC transfusion.